Postoperative nursing of a patient undergoing breast-conserving surgery for left-sided breast cancer (1例左侧乳腺癌保乳手术患者术后护理体会) - LI Yajing (李亚静); JIA Ruijing (贾瑞晶); CHEN Hong (陈宏) (Association of Integrative Nursing, 2023)
This paper summarized the postoperative nursing of a patient undergoing breast-conserving surgery for left-sided breast cancer. Key issues of postoperative nursing included pain management, infection prevention, skin care, prevention of deep venous thrombosis and psychological care. Targeted postoperative nursing interventions are effective in pain relief and prevention of complication of breast-conserving surgery for left-sided breast cancer. (本文总结1例左侧乳腺癌保乳手术患者术后护理经验, 包括疼痛护理、感染预防、皮肤护理、深静脉血栓预防、心理护理, 通过实施针对性护理, 有效缓解患者疼痛, 避免并发症, 对患者的早期康复有积极意义。)